Penerapan Model Pembelajaran Picture and Picture Berbantuan Media Audiovisual untuk Meningkatkan Penguasaan Konsep Siswa Sekolah Dasar - Rivaldo Paul Telussa; Selmyni H J Telussa; Cristiana Normalita de Lima (Musamus Journal of Primary Education, 2021)
This study is based on preliminary observations found in the field that the low value of mastery of the social studies concept. The research aims to know the concept mastery of material technology development in society by using the picture and picture learning model assisted by audiovisual media. This research was conducted at SD Inpres Nakupia. The sample was 19 students of grade IV. The data were collected using a test in the form of multiple choices, and it was analyzed descriptively using the Gain Normalization Test to see the improvement. The results showed that using the picture and picture learning model assisted by audiovisual media showed an increase in concept mastery which was seen in students with the highest score of 100 and the lowest score of 90, and the N-Gain test obtained 1.00 in the high category. Thus it can be concluded that the application of the picture and picture learning model assisted by audiovisual media shows an increase in the mastery of the concept of technological development in society in grade IV SD Inpres Nakupia.